MZF1 in the Dorsal Root Ganglia Contributes to the Development and Maintenance of Neuropathic Pain via Regulation of TRPV1 - Fei Xing; Hanwen Gu; Qin Niu; Xiaochong Fan; Zhongyu Wang; Jingjing Yuan; Zhisong Li; Ji-Tian Xu; Wei Zhang (Neural Plasticity)
Previous studies have demonstrated that myeloid zinc finger 1 (MZF1) in the dorsal root ganglion (DRG) participates in neuropathic pain induced by chronic-constriction injury (CCI) via regulation of voltage-gated K+ channels (Kv). Emerging evidence indicates that transient receptor potential vanilloid 1 (TRPV1) is involved in the development and maintenance of neuropathic pain. Although it is known that the transcription of TRPV1 is regulated by Kruppel-like zinc-finger transcription factor 7 (Klf7)—and that the structure of TRPV1 is similar to that of Kv—few studies have systematically investigated the relationship between MZF1 and TRPV1 in neuropathic pain. In the present study, we demonstrated that CCI induced an increase in MZF1 and TRPV1 in lumbar-level 4/5 (L4/5) DRGs at 3 days post-CCI and that this increase was persistent until at least 14 days post-CCI. DRG microinjection of rAAV5-MZF1 into the DRGs of naïve rats resulted in a decrease in paw-withdrawal threshold (PWT) and paw-withdrawal latency (PWL) compared with that of the rAAV5-EGFP group, which started at four weeks and lasted until at least eight weeks after microinjection. Additionally, prior microinjection of MZF1 siRNA clearly ameliorated CCI-induced reduction in PWT and PWL at 3 days post-CCI and lasted until at least 7 days post-CCI. Correspondingly, microinjection of MZF1 siRNA subsequent to CCI alleviated the established mechanical allodynia and thermal hyperalgesia induced by CCI, which occurred at 3 days postinjection and lasted until at least 10 days postinjection. Microinjection of rAAV5-MZF1 increased the expression of TRPV1 in DRGs. Microinjection of MZF1 siRNA diminished the CCI-induced increase of TRPV1, but not P2X7R, in DRGs. These findings suggest that MZF1 may contribute to neuropathic pain via regulation of TRPV1 expression in DRGs.